BENTUK PENYAJIAN TARI JEPIN BISMILLAH DALAM ACARA PERNIKAHAN DI DESA BELITANG 1 KABUPATEN SEKADAU KALIMANTAN BARAT - Pangestu, Hesty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The background of dance research Jepin Bismillah done is in the range of motion of the dance has a unique move with the position of the foot slightly hanging. In the middle of the dance, there is a reduction and addition of dancers aimed at introducing dancers to the bride. This study aims to describe motion, supporting elements, and implementation design.  This research uses descriptive method in the form of qualitative, and ethnokoreologi approach. Sources of research data are Maimunah, Syech Husein Bactib, Firmanto, Ardianan Ayang and Muhammad Firmansyah. Data collection techniques used are observation techniques, interviews and documentation. The instruments of data collection are observation, interview, camera and notebook. Techniques to test the validity of data using observational persistence, triangulation of sources and techniques. Data analysis techniques use data reduction, data display, and verification.  The form of presentation of Jepin Bismillah dance in the wedding, using the motion of the bride Cowl, Cover, Tahtim, Step 5, 9 and 4. The dress code used is kebaya clothes, songket and songket scarf. Makeup used like a solid powder and lipstick. Musical instruments used such as gambus and beruas, along with lyunan poetry. Dance shows can be displayed on the ground, stage or yard. This research will be implemented in SMA on SBK learning in the 2013 curriculum which consists of Core Competence and Basic Competence.       Keywords: The Arrangement Of Dance Performance, Jepin Dance ‘Bismillah.